Subverting patriachy: a comparative study of the novels of george eliot and toni morrison from a feminist perspective - Kennedy, J.M.; Veeramankai, S.Y. (University of Jaffna, 2016)
Women are still the largest among the oppressed social groups locally, nationally and globally. Family is the basic social institution which lays the foundation for suppression of women. With the father figure (God in religion) in the throne, it would be a blasphemy to question the authority, validity and the principles upon which family has been constituted. Right from the primitive age through the feudal one, family has been constructed, through different discursive practices as an unquestionable and holiest social institution. Literature is one of the pivotal discursive practices through which all hegemonic ideologies, including patriarchy have been produced, reconfirmed and sustained. Feminist writers rely much on challenging such hegemonic literary representations in changing the life conditions of women. George Eliot and Toni Morrison in their novels, provide ample scope for their female protagonists to reject male authority in family and to reverse the roles of gender imposed by patriarchy. This study, through comparison aims to show how these two women novelists, from different ages and cultures present alternative character models of women. Their women characters challenge the patriarchal norms and behavioural patterns of women as mothers, wives and daughters. The study compares the novels written by George Eliot and Toni Morrison to analyse how they subvert patriarchy through presenting rebellious women characters. It uses Marxist, feminist and gynocritical theories for textual interpretation. The gynocriticism look into the specific biological, psychological, linguistic and cultural experiences of women writers to interpret their texts. Comparison and textual interpretation are the methodologies used in the study. On top of the wide temporal, spatial and cultural differences, these writers portray characters that subvert and reverse the familial roles prescribed to women.
Keywords: Daughter hood; Gynocriticism; Familial roles of women motherhood; Subverting patriarchy; Wifehood